UPAYA PERCEPATAN PENINGKATAN KUALIFIKASI PENDIDIKAN DAN TENAGA KEPENDIDIKAN PENDIDIKAN NON FORMAL (PTK-PNF) - Soedijarto Soedijarto (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
In essential there is no difference between the professional competences of the formal education educators and the professional competences of the non-formal education educators. The significant differences between this two groups of educators are not in the competences of the educators but rather on the learners that they are responsible to deal with as well as on the various types of nonformal educational programs. The problems faced related to the effort to rise the competences of the non-formal educators are more complex than the effort to raise the competences of the nonformal education educators (teachers). For this, it is important for conducting national assessment to get the information on the spectrum of non-formal education educators. That includes Package A, B, & C, early child development and various non-formal educational courses. For Package A & B, predicted after the success of 9 years basic compulsory education, there will no more demand to run package A & B. For this, the educators for the program can be tackled in ad hoc way, but for others, serious effort need to be carried out, for this area of profession is really a new one.